Pengaruh Stakeholder terhadap Luas Pengungkapan Laporan Keberlanjutan pada Perusahaan yang Terdaftar di Indeks SRI-KEHATI, LQ45, JII, dan IDX BUMN20 Periode 2020–2022 - Hasjim, Deandra; Meiden, Carmel (Global Research on Economy, Business, Communication, and Information, 2025)
Starting in 2023, Jakarta will face air pollution causing 12,000 deaths. As a result, companies focus on creating sustainability reports to attract stakeholder attention. However, as of December 31 2021, only 154 companies had reported sustainability reports. This research aims to analyze the influence of stakeholders, including media, government ownership, institutional ownership, managerial ownership, and employee gender diversity, on the disclosure of sustainability reports in companies listed on SRIKEHATI, LQ45, JII (Jakarta Islamic Index), and BEI Index. This research uses multiple regression analysis of company sustainability report data and stakeholder characteristics from annual reports and company documents. The research results show that the media has a significant influence on the extent of disclosure of sustainability reports, while government ownership, institutional ownership, managerial ownership, and employee gender diversity do not have a significant influence on the extent of disclosure of company sustainability reports.